Metabolites from traditional Chinese botanical drugs with anti-hepatitis B virus activity - a review - Li, Nannan; Feng, Xue; An, Cheng; Liu, Guijian; Liu, Chao (Frontiers in Pharmacology, 2024)
Hepatitis B virus (HBV)-related liver disease poses a major threat to human health worldwide.Although interferon and nucleoside analogues are commonly administered for treating chronic HBV infection, their use is limited by considerable side effects, drug resistance and incapacity for HBV elimination. Hence, novel HBV therapeutics are urgently required. For numerous years, traditional Chinese botanical drugs have been widely used to treat HBV-related diseases. The natural metabolites derived from these traditional drugs exhibit significant anti-HBV effects and serve as potential novel drugs for treating HBV. For overall understanding the therapeutic potential of these metabolites, the anti-HBV effects and mechanisms of action of 107 natural metabolites are summarized in this article. Mechanistically, these natural metabolites exert their anti-HBV effects by influencing the expression and function of host and/or viral genes, which differs from the mechanism of action of nucleoside analogues. Indeed, combining natural metabolites with nucleoside analogues can exert synergistic effects. Accordingly, natural metabolites or their chemically modified derivatives represent potential novel drugs and adjuvants for anti-HBV treatment.